Konsepsi Profesi Arsitek Siswa Kelas IV SDN Petojo Selatan 01 Pagi: Studi Analisis Gambar dengan Menggunakan Aplikasi Construct 2) - Utami, Dinda Nuria; Nasyahrum, Andira Valenti; Hanif, Muhammad; Anggraini, Putri Dwi Ciska; Azizah, Wardah; Meilani, Ina (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2023)
Early exposure to various professions is essential. The effects can make it easier for children to recognize what they want for the future. It is also essential to teach them the value of the profession. The study studied the concept of grade iv elementary school students in the South Petojo region's profession. The study was conducted to discover misconceptions about the architectural profession among elementary school students in the research environment. This study aims to know if students understand the differences in the professions of architects, interior design, and construction workers. The method used in this study is qualitative. In all, the study of the fourth-grade architect's conception of 14 students suggests that most students already understand the difference between the profession of architect, builder, and interior design. The finds indicate that students already understand the third order of professions within construction (development). Students understood that the first order in the construction sphere was the architect, the second order was the construction worker, and the last order was interior design. The benefits of this study are that students can distinguish between architecture, interior design, and construction workers through the construction applications which belong to the ICT students' literacy.